THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLES AND PARENTS’ ATTENTION WITH MEASURING EQUIPMENT ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF AUTOMOTIVE ENGINEERING EXPERTISE PROGRAM OF STATE VOCATIONAL HIGH SCHOOL PIRI SLEMAN IN THE ACADEMIC YEAR 2013/2014 - Moh. Sulhan Haidi; Pairun Roniwijaya (Jurnal Taman Vokasi, 2014)
This research is aimed at finding out (1) the correlation  between students’ learning styles and measuring equipment achievement of the tenth grade students of Automotive Engineering Expertise Program of State Vocational High School Piri Sleman in the academic year 2013/2014; (2) the correlation between parents’ attention with measuring equipment achievement of the tenth grade students of Automotive Engineering Expertise Program of State Vocational High School Piri Sleman in the academic year 2013/2014; (3) the correlation between students’ learning styles and parents’ attention with measuring equipment achievement of the tenth grade students of Automotive Engineering Expertise Program of State Vocational High School Piri Sleman in the Academic Year 2013/2014.The kind of this research is correlation study and categorized as ex post facto. The population of the research was 105 students while the sample was 82 students counted from Isaac and Michael formula. The technique of sampling used in this research was simple random sampling. The technique of the data collection was questionnaire and documentation. Item validity was computed from product moment correlation. Item reliability was calculated by using alpha formula. The technique of data analysis used in this study was partial correlation and doubled correlation analyses. Precondition testing analysis (normality, linearity, and multi co linearity testing),Based on the data analysis, the results were as follows: (1) there is a positive and significant correlation between students’ learning styles (X1) and measuring equipment achievement (Y); (2) there is a positive and significant correlation between parents’ attention (X2) with measuring equipment achievement (Y); (3) there is a positive and significant correlation between students’ learning styles (X1) and parents’ attention (X2) with measuring equipment achievement (Y).